Towards promoting timely treatment: Uncovering the determinants of prompt malaria care seeking behavior among febrile children under-five years in Tanzania - Huda Omary; Suleiman Chombo; Pankras Luoga; Jackline Vicent Mbishi; Heavenlight A. Paulo; John Andrew; Abdallah Zacharia; Isaac Y. Addo (PLoS ONE, 2025)
Background Prompt diagnosis and effective treatment within 24 hours of fever onset is crucial for reducing malaria-related morbidity and mortality in under five children. However, research on the prompt care-seeking behaviors and their determinants in this demographic is limited. This study examined the prevalence of prompt care-seeking behaviors among under five febrile children in Tanzania and the associated determinants. Methods This cross-sectional study analyzed data from the 2022 Tanzania Demographic and Health Survey (TDHS), including a nationally representative and weighted sample of 1,050 under-five children who experienced fever within two weeks prior to the survey. A weighted univariable and multivariable modified Poisson regression model with robust estimator was used to examine the association between prompt care seeking behaviors and explanatory variables, including child and caregivers’ factors. Results The prevalence of prompt care seeking for febrile children was 43.2%. Caregivers of female children had 18% less prevalences of seeking prompt care (95% CI 0.68–0.98) compared to caregivers with their male children. Caregivers aged 25–34 and 35–49 years had 36% (95% CI 1.05–1.78) and 61% (95% CI 1.16–2.23) higher prevalences of seeking prompt care for their children respectively, compared to younger caregivers aged 15–24 years. Caregivers with at least primary education had 50% (95% CI 1.12–2.02) higher prevalences of seeking prompt care compared to those with no formal education. Additionally, an increase in one household member was associated with a 3% increase in the prevalence of seeking prompt malaria care (95% CI 1.01–1.05). Conclusion In Tanzania, female children under five experience delays in care-seeking for malaria, whereas older and more educated caregivers are more likely to seek timely treatment for their children. To enhance health outcomes in this vulnerable group, targeted interventions should prioritize raising awareness among caregivers, particularly younger ones and prompting equitable care seeking to all children regardless of sex.